2010
DOI: 10.3109/09638281003611086
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial validation of the Children Participation Questionnaire (CPQ)

Abstract: Purpose. To develop and test the psychometric properties of a parent-reported questionnaire measuring participation of preschool children (Children Participation Questionnaire; CPQ) aged 4-6 years in their everyday activities. Methods. Reliability was tested by Cronbach's a and by test-retest. Construct validity was computed by known group differences analysis. Convergent and divergent validities were calculated by correlation with the Vineland Adaptive Behaviour Scale (VABS). Two hundred thirty-one children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 41 publications
1
92
1
4
Order By: Relevance
“…Our results suggest that therapists should expect children (especially very young children) and their parents to disagree somewhat, so supporting previous studies (Dunford et al, 2005;Missiuna et al, 2006) that found that the perceptions of children do not necessary coincide with those of their parents. Indeed, children may be satisfied with their performance when significant adult figures in their lives (parents, teachers) are not, as was previously found by Rosenberg et al (2010).…”
Section: Content Validitymentioning
confidence: 49%
See 3 more Smart Citations
“…Our results suggest that therapists should expect children (especially very young children) and their parents to disagree somewhat, so supporting previous studies (Dunford et al, 2005;Missiuna et al, 2006) that found that the perceptions of children do not necessary coincide with those of their parents. Indeed, children may be satisfied with their performance when significant adult figures in their lives (parents, teachers) are not, as was previously found by Rosenberg et al (2010).…”
Section: Content Validitymentioning
confidence: 49%
“…The CPQ (Rosenberg et al, 2010;Rosenberg & Bart, 2015) is a parent-completed questionnaire constructed according to the OTPF classification system and designed to measure the participation of preschool children aged 4 to 6 years (Rosenberg et al, 2010). The CPQ has been adapted to create the CPQ-School version, which assesses the participation patterns of schoolchildren aged 6 to 9 years (Rosenberg & Bart, 2015) Intra-class correlations of 0.71 -1.00 indicate that it has good temporal stability, too.…”
Section: Children Participation Questionnaire (Cpq)mentioning
confidence: 99%
See 2 more Smart Citations
“…teigia, kad dalyvumo didinimas yra pagrindinis vaikų reabilitacijos tikslas. Vaikystėje dalyvumas yra susijęs su vaiko vystymusi ir augimu, todėl planuojant reabilitaciją ir iškeliant jos tikslus, turi būti orientuojamasi daugiau į dalyvumo didinimą [25].…”
Section: Tfk-vj Skyriaiunclassified